Dynamical behaviors of an epidemic model for malware propagation in wireless sensor networks - Zhou, Ying; Wang, Yan; Zhou, Kai; Shen, Shou-Feng; Ma, Wen-Xiu (Frontiers in Physics, 2023)
To explore malware propagation mechanisms in networks and to develop optimal strategies for controlling the spread of malware, we propose a susceptible-unexposed-infected-isolation-removed epidemic model. First, we establish a non-linear dynamic equation of malware propagation. Then, the basic reproductive number is derived by using the next-generation method. Finally, we carry out numerical simulations to observe the malware spreading in WSNs to verify the obtained theoretical results. Furthermore, we investigate the communication range of the nodes to make the results more complete. The optimal range of the nodes is designed to control malware propagation.